Mapping and predicting mortality from systemic sclerosis. Issue 11 (23rd August 2017) - Elhai, Muriel; Meune, Christophe; Boubaya, Marouane; Avouac, Jérôme; Hachulla, Eric; Balbir-Gurman, Alexandra; Riemekasten, Gabriela; Airò, Paolo; Joven, Beatriz; Vettori, Serena; Cozzi, Franco; Ullman, Susanne; et al.
Abstract : Objectives: To determine the causes of death and risk factors in systemic sclerosis (SSc). Methods: Between 2000 and 2011, we examined the death certificates of all French patients with SSc to determine causes of death. Then we examined causes of death and developed a score associated with all-cause mortality from the international European Scleroderma Trials and Research (EUSTAR) database. Candidate prognostic factors were tested by Cox proportional hazards regression model by single variable analysis, followed by a multiple variable model stratified by centres. The bootstrapping technique was used for internal validation. Results: We identified 2719 French certificates of deaths related to SSc, mainly from cardiac (31%) and respiratory (18%) causes, and an increase in SSc-specific mortality over time. Over a median follow-up of 2.3 years, 1072 (9.6%) of 11 193 patients from the EUSTAR sample died, from cardiac disease in 27% and respiratory causes in 17%. By multiple variable analysis, a risk score was developed, which accurately predicted the 3-year mortality, with an area under the curve of 0.82. The 3-year survival of patients in the upper quartile was 53%, in contrast with 98% in the first quartile. Conclusion: Combining two complementary and detailed databases enabled the collection of an unprecedented 3700 deaths, revealing the major contribution of the cardiopulmonary system to SSc mortality. We also developed a robust score to risk-stratify these patients and estimate their 3-year survival. With the emergence of new therapies, these important observations should help caregivers plan and refine the monitoring and management to prolong these patients' survival.